Primitive Neuroectodermal Tumor of the Pancreas: A Case Report and Review of the Literature. (26th May 2015) - Teixeira, Uirá; Goldoni, Marcos; Unterleider, Michelle; Diedrich, João; Balbinot, Diogo; Rodrigues, Pablo; Monteiro, Rodolfo; Gomes, Daniel; Sampaio, José; Fontes, Paulo; Waechter, Fábio
Abstract : Primitive neuroectodermal tumors (PNETs) are presented as rare malignant neoplasms. In unusual cases, those neoplasms may arise in solid organs containing neuroendocrine cells, such as the pancreas. Herein the case of a 28-year-old patient that underwent gastroduodenopancreatectomy after the diagnosis of a huge mass (PNET) located in both head and body of the pancreas is reported. This is the 19th case of pancreatic PNET reported in literature.